A disposable modified screen-printed electrode using egg white/ZnO rice structured composite as practical tool electrochemical sensor for formaldehyde detection and its comparative electrochemical study with Chitosan/ZnO nanocomposite. (February 2022) - Padmalaya, G.; Vardhan, Kilaru Harsha; Kumar, P. Senthil; Ali, M. Ajmal; Chen, Tse-Wei
Abstract: In this study, Chitosan/ZnO nanocomposite (Ch/ZnO) and egg white/ZnO rice structured composite was synthesized by simple wet chemical technique and characterised by various techniques. A comparative electrochemical analysis were carried out and determined that egg white/ZnO rice structured composite modified screen printed electrode (SPCE) showed good electrochemical behaviour. The electrochemical activity of egg white/ZnO rice structured composite SPCE was investigated for the oxidation-reduction of formaldehyde in alkaline media using cyclic voltammetry (CV).Their unique electrocatalytic activity for the formaldehyde found to exhibit 254 mV cathodic current response towards low negative potentials. Based on these results, a novel screen printed sensor (Egg white albumin/ZnO rice structured composite) for the determination of formaldehyde was analysed using differential pulse voltammetry (DPV). The sensor response was linear from 0.001 mM to 0.005 mM with limit of detection (LOD) 6.2 nM and their sensitivity was found to be 770.68 mM/μA. The developed electrochemical formaldehyde sensor was successfully applied as working electrode in cyclic voltammetric determination of formaldehyde in urine samples. The sensor is selective, inexpensive, stable over several days and disposable as well as simple to manufacture and operate. The system described here can be easily be adapted to other substrates and used as practical tool for formaldehyde analysis. Graphical abstract: Image 1 Highlights: A novel approach using Ch/ZnO nanocomposite and Egg albumin/ZnO rice structured composite modified SPCE has been proposed. Increased electrochemical behavior was noticed for Egg albumin/ZnO rice structured composite modified SPCE. The sensor exhibited high sensitivity of 770.68 μA/mM with linear range 0.001 mM–0.005 mM. The obtained electrochemical sensor has been tested for real-time analysis in urine samples. Thus proposed developed electrode system aimed to serves as a solid foundation for formaldehyde detection.